Patterns of real-time occupational ultraviolet radiation exposure among a sample of outdoor workers in New Zealand - Hammond, V.; Reeder, A.I.; Gray, A. (Public health (London), 2009)
Exposure to solar ultraviolet radiation (UVR) is an occupational health and safety issue for outdoor workers since excessive exposure is associated with negative health outcomes, including eye conditions and skin cancers. The objective of this research was to describe the pattern of UVR exposure experienced by outdoor workers from selected occupations in New Zealand in order to identify the impact of behaviour and work conditions on exposure. This paper reports on the occupational UVR exposure arm of a dual arm cross-sectional study that also examined workers' sun protection practices. For five consecutive working days in January–March 2007, electronic dosimeters were used to record the time-stamped UVR exposure of a sample of 77 outdoor workers from three occupations (building, horticulture and roading) in Central Otago, New Zealand. The geometric mean total daily UVR exposure (between 1100 and 1600 h) was 5.32 standard erythemal doses (SED; 95% reference range 0.28–19.97 SED). The geometric mean total daily UVR exposure as a percentage of the total daily ambient UVR was 20.5% (95% confidence interval 1.4–83.0%). Personal UVR exposure dipped between 1200 h and 1300 h – the same time that ambient UVR peaked – indicating the effect of shade seeking over the lunch period. Personal UVR exposure peaked between 1400 h and 1500 h, alongside decreasing ambient UVR levels, suggesting the influence of behavioural rather than climatic factors. The difference in workers' exposure between 1200 h and 1300 h, and 1400 h and 1500 h was statistically significant for both measured personal exposure ( P < 0.005) and exposure calculated as a percentage of concurrent available ambient UVR ( P < 0.005). All the workers in this study recorded mean daily UVR exposure in excess of the current recommended occupational exposure limits. Only a minority of workers sought shade during their lunch break; most remained in highly exposed conditions. There is no evidence that work tasks which involve substantial sun exposure are being scheduled outside the high UVR period.